The 2008 Election in Florida: Change! But Only at the Top of the Ticket - Crew, Robert E. (Hamilton Books, 2011)
During 2008, the Democrats achieved in Florida a goal that had eluded them in all but three of the national elections since 1964: victory in the presidential race. Despite this success, the Republicans retained their dominance in the U.S. Congress and in the Florida State Legislature. The 2008 Elections in Florida utilizes multiple types of data to provide an explanation for the disparate outcomes of these elections. The book chronicles changes in voter registration and turnout over time and compares the electoral behavior of groups in Florida to that in the nation as a whole. It examines the importance of legislative apportionment, term limits and incumbency to the outcome of congressional and state legislative races and provides important clues to the future of electoral behavior in one of the nation's most important states.